MEMPERKUAT PENGAWASAN: MEMETAKAN KEDUDUKAN INSPEKTORAT DALAM MENJAMIN AKUNTABILITAS DAN INTEGRITAS PADA ERA TRANSPARANSI - Fujilestari, Noer Apptika; Rochaeni, Atik; Ramdani, Wisam (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Supervision is one of the important pillars in realizing good governance and integrity. The Inspectorate is an internal government supervisory institution that has an important role in ensuring that government administration is transparent, accountable, and free from corruption. In the era of transparency, the position of the inspectorate needs to be strengthened so that it can carry out its supervisory function effectively and independently. The independent position of the inspectorate can guarantee objectivity and effectiveness in carrying out supervisory duties. This research aims to examine the position of inspectorates in ensuring accountability and integrity in the era of transparency. This research uses qualitative research methods by taking sources from literature studies. The research results show that the position of the inspectorate in ensuring accountability and integrity in the era of transparency needs to be strengthened. This can be done by strengthening the independence of the inspectorate, namely by changing its position to be independent of the government or political party in power. Then improve the quality of human resources and an adequate inspectorate budget. As well as increasing public understanding of the role of inspectorates in supervising government administration. These efforts need to be carried out continuously to create a strong and independent inspectorate so that it can become a bulwark to prevent corruption and maladministration in government administration.